Blending Mon and Thai cultural practices in Piphat Mon performance traditions of Central Thailand - Chayuti Tassanawongwara; Hanafi Hussin (Cogent Arts & Humanities)
Piphat is an ensemble in traditional Thai music, is perceived as central Thai music and represents court tradition based on idiophones and membranophones. Similarly, the Piphat Mon is Piphat music blended with Mon musical influence. There have been questions about whether Piphat Mon is part of the Mon or Thai music traditions. In general perception, Piphat Mon plays a significant role in the performance of traditional Thai music and is regarded as sacred music for funerals. The Mon people perceived the music as a legacy from their ancestors since escaping from their homeland to Siam centuries ago. Through time and many layers of acculturation, adoption and adaptation, Piphat Mon incorporated Thai elements and became identic to Thai culture. Thai people commonly use the Piphat Mon to serve Thai funerals. The Mon people play Piphat Mon mainly for sacred rituals such as ghost dance (rum pee) and other ceremonies. This paper examines Piphat Mon present status and significance in the Thai musical scenery. The study employed qualitative research and data collection, accomplished by observation, participant observation, and in-depth interviews. Findings show that Thai and Mon elements blended in musical instruments, melodies, repertoires, lyrics, and language. The elements adopted, adapted, and harmoniously integrated into Thai society. With regard to the classical element, the Piphat Mon is regarded as an invaluable, remarkable music ensemble, and it is considered an image of Thai music traditional values associated with Mon culture. Therefore, Piphat Mon can maintain Thai cultural identity through musical performance while promoting harmony between the Thai and Mon people.